Double stranded RNA is processed differently in two oyster species. (November 2017) - Masood, Muhammad; Herberstein, Marie E.; Raftos, David A.; Nair, Sham V.
Abstract: Ostreid herpes virus causes serious disease in the Pacific oyster ( Crassostrea gigas ), but not in the Sydney Rock Oyster ( Saccostrea glomerata ). To investigate differences in disease progression, we injected oysters with double stranded RNA (dsRNA). dsRNA is known to mimic viral infection, and can evoke immune responses when Toll-like receptors detect the dsRNA, leading to the production of type 1 interferon and inflammation cytokines. The uptake and processing of dsRNA was tracked in gill and mantle tissue of Crassostrea gigas and Saccostrea glomerata after injection of fluorochrome labelled poly (I:C) dsRNA. The two species showed significant differences in tissue uptake and clearance, and differences in immune responses confirmed by real time PCR. These results showed that S. glomerata was more efficient in processing dsRNA than C. gigas, and that the gill tissue is an important site of dsRNA processing and response. Highlights: Saccostrea glomerata is more efficient in processing dsRNA than Crassostrea gigas. Oyster gill tissue is an important site of dsRNA processing and response. There is a significant three-way interaction between species, time and tissue in processing of fluorescence labelled dsRNA. RNAi pathway is operating both at transcriptomic and proteomic level.